Application of nuclear physics methods and NSC KIPT accelerators for investigation of solid composition - Skakun, N.A.; Svetashov, P.A. (Вопросы атомной науки и техники, 2003)
The results of application of nuclear physics methods and NSC KIPT accelerators in the fields of investigation of metals and alloys, semiconductors, oxidic metals and magnetic materials are outline. The results and potentialities of these methods for determination of concentration and distribution of micro quantities of elements and isotopes, investigation of features and properties of simplest defects are presented. The beams of (1–3) MeV hydrogen and helium ions were used. Element and isotope identification was realized by means of Rutherford backscattering, resonance nuclear reactions and incident ions induced X – ray radiation. Викладаються результати застосування методів ядерної фізики і прискорювачів ННЦ ХФТИ в області металів і сплавів, напівпровідників, метало оксидних з'єднань, магнітних матеріалів. Результати і можливості використання цих методів для визначення концентрації і розподілу мікрокількостей елементів і ізотопів, дослідження характеристик і властивостей найпростіших дефектів. Застосовувалися іони ізотопів водню і гелію з енергією в інтервалі (1...3) МеВ Ідентифікація елементів і ізотопів здійснювалася за допомогою зворотного розсіювання, резонансних ядерних реакцій і характеристичного рентгенівського випромінювання, порушуваного прискореними іонами. Излагаются результаты применения методов ядерной физики и ускорителей ННЦ ХФТИ в области металлов и сплавов, полупроводников, металлооксидов, магнитных материалов. Представлены результаты и возможности использования этого научного направления для определения концентрации и распределения микроколичеств элементов и изотопов, исследования характеристик и свойств простейших дефектов и др. вопросы. Применялись ионы изотопов водорода и гелия с энергией в интервале (1...3.5) МэВ. Идентификация элементов и их изотопов осуществлялась с помощью обратного рассеяния, резонансных ядерных реакций и характеристического рентгена, возбуждаемого ускоренными ионами.